2011
DOI: 10.1063/1.3664117
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode quantum cascade lasers employing a candy-cane shaped monolithic coupled cavity

Abstract: Articles you may be interested inCoupled-cavity terahertz quantum cascade lasers for single mode operation Appl. Phys. Lett. 104, 241102 (2014); 10.1063/1.4884056 Single-mode quantum cascade lasers employing asymmetric Mach-Zehnder interferometer type cavities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…In summary, we have shown that for two coupled cavities of different FSRs, the overlapping of their resonances do not typically favor lasing, resulting in an inverse Vernier effect. The suppression of these overlapping resonances can also lead to an increased FSR and possibly singlemode lasing, as found in previously experiments [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In summary, we have shown that for two coupled cavities of different FSRs, the overlapping of their resonances do not typically favor lasing, resulting in an inverse Vernier effect. The suppression of these overlapping resonances can also lead to an increased FSR and possibly singlemode lasing, as found in previously experiments [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 75%
“…The only differences are: (i) a different β factor is needed to capture the phase and amplitude change of the light after a round trip in the slab cavity, including the effect of the radiation loss through the end facets; and (ii) the clockwise and counterclockwise waves in the micro-ring/micro-disk cavity are coupled by a slab resonance. More specifically, the equivalence of the threshold condition (5) or (6) is…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Альтернативные подходы к формированию одночастотных ККЛ основаны на применении фотонных кристаллов [4], кольцевых резонаторов [3], связанных резонаторов [5], асимметричных интерферометров Маха−Цендера [6]. Результаты по формированию лазерных резонаторов сложной формы, в том числе арочных квантово-каскадных лазеров, состоящих из линейных и полукольцевых участков, представлены в работах [7][8][9].…”
Section: поступило в редакцию 28 января 2019 г в окончательной редакunclassified
“…To overcome this limitation of DFB-QCLs, an array of DFB-QCLs with a broad tuning range has been reported[22,135], while this method poses fabrication challenges in ensuring each ridge laser working properly and extra efforts are needed to spatially combine the beams from the array of DFB-QCLs for better collimation[136][137].Despite the large tuning range of EC-QCLs, the mechanical parts within the EC-QCLs cavity make them vibration sensitive and comparatively expensive. One effective approach to overcome these limitations is to utilize Vernier-effect tuning mechanism, based on which the coupled-cavity QCLs and the SG-QCLs were proposed[103][104][138][139]. Nevertheless, both approaches have their intrinsic drawbacks which severely limit their real field applications.…”
mentioning
confidence: 99%